OPTIMALISASI MEDIA DIGITAL RENUNGAN.MY.ID SEBAGAI SARANA PENGINJILAN MANDIRI DI ERA DIGITAL - Theo Pilus Candra (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
The purpose of conducting this community service (PkM) activity is as a form of implementing digital ministry in synergy between academics and GPdI Eben Heazer Karangpandan as well as JKI Maranata Matesih in Karanganyar Regency, Central Java. This activity, carried out in the digital era, aims to optimize digital media through the renungan.my.id platform as a means of independent evangelism and to improve the spiritual discipline of the local congregation. The main problem faced by both partners is the lack of productive smartphone utilization for faith growth and the limited access to practical daily Bible literacy materials. The method of implementing the activity is realized through the forms of material presentation (education), direct practice of operating website features, simulation of testimonial content distribution, and regular interactive discussions. Overall, the PkM activity received a positive and enthusiastic response from the pastors, youth commission committee, and all members of the local congregation, marked by an increase in technical understanding and spiritual commitment to cyber-based independent evangelism.